POTENSI DAN STRATEGI PENGEMBANGAN BANK SYARIAH DI INDONESIA - Anny Ratnawati (School of Business, Bogor Agricultural University (SB-IPB), 2005)
At the present, Indonesia operate dual banking system that are conventional banking system with its interest rate runs side by side with the Islamic banking with the profit-sharing/non-interest system of its own. The development of Islamic banking should be based on market driven by driving the community demand that always considering the banking prudential principle. The development of Islamic bank will encourage the development of real sector as well because the basis of profit-sharing system is the activities of real sector, not from investment of other sector (non real sector), case in point the rate of obligation and/or the rate of Certificate of Central Bank. In general, community’ s respond toward Islamic bank is good relatively that shown by the trend of Third Parties Funding and Financing to Deposit Ratio with low level of Non Performing Loan. This study assess the consumer’s preference toward both conventional and Islamic Banking, in related with analysis of potency and development strategy of Islamic banking in Indonesia. The analysis of data by using qualitatively (descriptive) analysis, cross tabulation and logistic regression model. In general, community’s attitude toward interest rate system still ambiguous, that are interest rate is contrary to ‘syariah of Islam‘, meanwhile in banking transaction they still use conventional system. The reasons that motivate consumer to adopt Islamic banking related to professionalism of bank, security and pleasure in doing transaction, strategic location and the implementation of syariah system. However, community still has difficulties to comprehend the technical term of Islamic banking. Thus, socialization and education process about economic system of Islam (syariah economic) designate necessary requirement in encourage the development of Islamic banking in the future.